Body distribution of SiO2–Fe3O4 core-shell nanoparticles after intravenous injection and intratracheal instillation. Issue 5 (27th May 2016) - Smulders, Stijn; Ketkar-Atre, Ashwini; Luyts, Katrien; Vriens, Hanne; De Sousa Nobre, Sonia; Rivard, Camille; Van Landuyt, Kirsten; Baken, Stijn; Smolders, Erik; Golanski, Luana; Ghosh, Manosij; Vanoirbeek, Jeroen; et al.
Abstract: Nano-silicon dioxide (SiO2 ) is used nowadays in several biomedical applications such as drug delivery and cancer therapy, and is produced on an industrial scale as additive to paints and coatings, cosmetics and food. Data regarding the long-term biokinetics of SiO2 engineered nanoparticles (ENPs) is lacking. In this study, the whole-body biodistribution of SiO2 core-shell ENPs containing a paramagnetic core of Fe3 O4 was investigated after a single exposure via intravenous injection or intratracheal instillation in mice. The distribution and accumulation in different organs was evaluated for a period of 84 days using several techniques, including magnetic resonance imaging, inductively coupled plasma mass spectrometry, X-ray fluorescence and X-ray absorption near edge structure spectroscopy. We demonstrated that intravenously administered SiO2 ENPs mainly accumulate in the liver, and are retained in this tissue for over 84 days. After intratracheal instillation, an almost complete particle clearance from the lung was seen after 84 days with distribution to spleen and kidney. Furthermore, we have strong evidence that the ENPs retain their original core-shell structure during the whole observation period. This work gives an insight into the whole-body biodistribution of SiO2 ENPs and will provide guidance for further toxicity studies.